Circular Use of Resources Theoretical and Practical Approaches of Sustainable Technologies, Business Models and Organizational Innovations - Popp, József H.c; Csaba, Fogarassy; Finger, David Christian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Circular solutions are essential to tackle the eminent challenges of depleting resources and emerging environmental problems. The complex nature of material and energy systems and the changing of economic and technological conditions differ among countries and, therefore, lead to the application of vastly different practices in developed and rapidly developing countries of the world. A wide variety of theoretical approaches can be used to facilitate a shift from the linear use of resources to circular systems, e.g., circular product planning, life cycle planning, sharing and platform economy, refurbishing, and remanufacturing, to name but a few. The introduction and examination of circular solutions can be based on theoretical models in order to guarantee ensure successful application. Successful application of innovative technology approaches, business solutions, and organizational development can be facilitated through theoretical models and new scientific results that support innovation processes. This Special Issue reprint focuses on sustainable and innovative methods which help and enable the proper use and recovery of resources. We present a collection of research papers, reviews, research reports, and case studies that introduce or discuss circular solutions for the sustainable use of resources.